Dinero Endógeno En Un Esquema Coherente De Existencias Y Flujos - Lavoie, Marc (2002)
This paper studies one method to model monetary macroeconomics, similar to belong to Wynne Ciodley. This method, based on a transaction matrix, ensure that all flows come from and go to some place, so there are not black holes. The method is used to handle some issues. It shows that there can exist one money demand separated by portfolio (stock), but not one independent of the rest of the world. Itis used to show that there couldn't be a supply excess of credit; to manage credit for speculation and high liquidity preference; to highlight that endogenous money at fixed interest rates is compatible with. any deficit of public sector; to show that, even though banks have liquidity rules, more credit amount doesn't introduce higher interest rates. In conclusion, the paper shows that many asseverations made by horizontalistas authors are confirmed when a totally countable scheme is established to evaluate them